2017
DOI: 10.1183/13993003.01232-2017
|View full text |Cite
|
Sign up to set email alerts
|

Plain packaging of tobacco products in the European Union: an EU success story?

Abstract: 10 For a list of the ERS Tobacco Control Committee members see the Acknowledgements section. 11 For a list of the ENSP Scientific Committee Members see the Acknowledgements section.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The UK Department of Health estimates that standardised packaging will have a net benefit to government of £25 billion ten years post-implementation (Department of Health, 2015). It is critical that countries robustly evaluate the impacts of this measure (Vardavas et al 2017) and do so over the longer term; a major limitation identified in a Cochrane review was the absence of research exploring the longer-term impacts of standardised packaging (McNeill et al 2017). While our findings provide support for standardised packaging during the transition period, research is needed to explore the intended and any unintended consequences of this policy in the UK (and elsewhere) after it has been fully implemented.…”
Section: Discussionmentioning
confidence: 87%
“…The UK Department of Health estimates that standardised packaging will have a net benefit to government of £25 billion ten years post-implementation (Department of Health, 2015). It is critical that countries robustly evaluate the impacts of this measure (Vardavas et al 2017) and do so over the longer term; a major limitation identified in a Cochrane review was the absence of research exploring the longer-term impacts of standardised packaging (McNeill et al 2017). While our findings provide support for standardised packaging during the transition period, research is needed to explore the intended and any unintended consequences of this policy in the UK (and elsewhere) after it has been fully implemented.…”
Section: Discussionmentioning
confidence: 87%
“…In the EU, most of the measures transposed and implemented were not designed to undermine the relationship of smokers with their specific brand, which could act as a shield against tobacco cessation 9 . Meanwhile, measures such as plain packaging, that could lead to a direct change in brand loyalty, are not compulsory and were left in charge of each country by the TPD 33 . This may result in delays and interference of the tobacco industry in the process of adopting plain packaging 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, measures such as plain packaging, that could lead to a direct change in brand loyalty, are not compulsory and were left in charge of each country by the TPD 33 . This may result in delays and interference of the tobacco industry in the process of adopting plain packaging 33 .…”
Section: Discussionmentioning
confidence: 99%
“…48 In other words, plain packaging removes all marketing elements, including brand, colours and logos. 49 Malaysia is still in progress for implementation of plain packaging. Plain packaging is said to be effective to reduce smoking among smokers and prevent initiation of smoking among non-smokers.…”
Section: Suggestion To Overcome Early Initiation Of Smokingmentioning
confidence: 99%